Uso do NDVI para estimativa da biomassa de pastagens de inverno no município de Vacaria-RS - Lima, Caroline Silveira de (2023)
The quantification of the spatial variability of forage biomass production, vegetation indices and soil properties can help in pasture management practices such as rotation, nutrient management and yield forecast. The objective of the present work was to estimate the biomass of winter pastures through the Normalized Difference Vegetative Index (NDVI) obtained with an active proximal sensor. The experiment was conducted in the field, 2019 harvest in the municipality of Vacaria, Rio Grande do Sul, in the experimental area of Campus 2 of the University of Caxias do Sul. Weekly assessments were carried out to monitor pasture growth, measuring height using a graduated ruler and NDVI readings using a Flexum, Falker terrestrial equipment. Seven treatments were tested, namely: T1: Azevem LE 284; T2: Azevem KLM 138; T3: Azevem Winter Star; T4: Oat IAPAR 61; T5: Supreme Oats; T6: Milton oats; T7: Oat and ryegrass intercropping. The experimental design was in randomized blocks, with four replications of each treatment. The evaluated variables were determination of biomass through the NDVI index and height. The results showed a positive linear correlation between NDVI and height. In the regression analysis, a coefficient of determination R² of 0.3785 was found between NDVI and height. The results indicated that the use of the NDVI index with the active proximal sensor can be a promising tool in estimating the biomass of winter pastures, up to the first cut.